Introductory Guide to Sanitation Marketing - Devine, Jacqueline; Kullmann, Craig (World Bank, Washington, DC, 2014)
Sanitation marketing is an emerging field with a relatively small group of practitioners who are learning by doing. With an introductory guide to sanitation marketing, the Water and Sanitation Program (WSP) seeks to contribute to the field by sharing practical guidance on the design, implementation, and monitoring of rural sanitation marketing programs at scale in India, Indonesia, and Tanzania, plus additional projects implemented in Cambodia and Peru. Author's goal for this guide and toolkit is to: define sanitation marketing and the key components of sanitation marketing; initiative; provide an overall framework for scaling up rural sanitation programs and the justification for using a sanitation marketing approach; explain the steps needed to design, implement, and monitor sanitation marketing programs at scale; and highlight key challenges and recommend solutions. The print guide emphasizes at scale throughout. Although the concept of scale will be applied differently in each country, the focus should be on thinking big enough from the beginning to plan interventions that can be replicated effectively and efficiently across an entire country.